Assessment of organochlorine pesticides in blood and tumor of breast cancer patients and control subjects from Punjab, Pakistan - Khalid, Anam; Abbasi, Naeem Akhtar; Jamil, Nadia; Syed, Jabir Hussain; Qadir, Abdul; Ahmad, Sajid Rashid (Environmental geochemistry and health, 2025)
In this cross-sectional study, relationship of organochlorine pesticides (OCPs) with breast cancer incidence is assessed by investigating their levels in tumor and blood serum of breast cancer patients and comparing them with blood serum of control subjects. A total of forty breast cancer patients and ten control individuals were recruited from different districts of Punjab, Pakistan. All the samples were analyzed for α- β- and γ-HCH, HCB, cis- and trans -Chlordane, α- and β-endosulfan, o,p- and p,p -DDE, o,p - and p,p -DDD and o,p -and p,p -DDT. In addition, sociodemographic along with some haematological and clinical parameters were obtained from patients to assess their possible relationship with breast cancer. Our results showed tumor with highest mean (min–max) concentrations (ng g −1 lw) of ƩOCPs at 114.01 (0.67–23.85) followed by blood serum of patients 90.08 (0.14–18.62) compared to blood serum of control 5.71 (ND-1.46) respectively. In this study p,p -DDE was dominant congeners in tumor, o,p -DDE in blood serum of patients and α-endosulfan in blood serum of control individuals. Haematological parameters such as chloride, sodium and potassium ions in blood were moderately associated with ∑DDD concentration in tumor. Similarly, sociodemographic as well as clinical variables reflects limited relationship with OCPs level in patients and control. It is concluded that the elevated concentrations of OCPs in tumor and blood serum of breast cancer patients compared to control subjects illustrate potential association of OCPs with breast cancer in Pakistan. However, in addition to pollutants exposure certain confounding factors including clinical and sociodemographic parameters may also contribute in breast cancer incidence which should be elucidated in future intensive investigations.